Determining the effect of online tourism brands' use of social media marketing on consumers/tourists' decision making process. - Goliath, Junaid (The IIE, 2022)
Social media has redefined how the practice of communication is conducted in business. Businesses can effectively and efficiently communicate their products and services to meet customers' needs at every point of desire. While at the same time, to manage customer satisfaction, consumers can post their concerns and receive a response which enhances customers satisfactions (Verizon, 2020). Social media has proven to be a valuable source of information for consumers in their purchase decision-making, especially in complex buying behaviour (Voramontri & Klieb, 2019). Therefore this applies to consumers' decisions when making travel arrangements. There is a need to understand the new consumer behaviour in terms of decision-making, purchase preferences, tourism risk perceptions and the factors influencing consumers’ purchase decisions (Meng et al., 2021).A cross-sectional self-administered survey design was used for the study. Quantitative research gathers data from current and potential participants. The survey was developed using evidence from previous research and the steps indicated in the EKB consumer decision-making process model. The research found that social media marketing on social media sites makes the evaluation of alternatives to online tourism products and services easier and therefore makes the decision to purchase faster. This finding is important for tourism industry organisations, specifically in the post-Covid era, as the tourism industry attempts to recover.
Keywords: Consumer behavior; Business communication; Customer experience; Buying behavior; Purchase intentions